Significance of serum mesothelin in an asbestos-exposed population in the Czech Republic - Jakubec, Petr; Pelclova, Daniela; Smolkova, Petra; Kolek, Vitezslav; Nakladalova, Marie (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2015)
AIMS: Pleural mesothelioma is a highly aggressive and difficult-to-treat form of cancer induced by asbestos in 80-90% of cases. The population group most at risk of the condition are asbestos-exposed workers. Mesothelin or soluble mesothelin-related protein (SMRP) is studied as a potential marker of mesothelioma in the at-risk population. METHODS: The study comprised 239 subjects with a mean duration of occupational exposure to asbestos of 19.9 years. In all of them, a complete medical history was taken, focused on exposure duration and a physical examination, a chest X-ray or other imaging investigations and a lung function test were performed. Their serum SMRP levels were measured and biopsy samples were taken to diagnose pleural disease. Based on the above examinations, the subjects were classified into subgroups and serum SMRP concentrations were statistically analyzed with respect to individual parameters. RESULTS: In asbestos-exposed individuals, mesothelin levels were significantly higher in those with pathological X-ray findings than in those with normal X-ray results (0.78 ± 0.63 vs. 0.50 ± 0.35, P<0.0001). The group of patients with benign disease had statistically significantly higher mesothelin levels than those with normal X-ray findings (0.755 ± 0.543 vs. 0.50 ± 0.35, P<0.001). In the group with present malignant processes, mesothelin levels were higher than in individuals with benign disease (1.19 ± 0.89 vs. 0.76 ± 0.54, P=0.015). Only a weak correlation was found between mesothelin levels and asbestos exposure duration. There were relatively high sensitivity and high specificity (75% and 90.6%, respectively) of serum mesothelin for pleural mesothelioma. However, given the small number of mesothelioma cases in the group, the results cannot be considered as statistically significant. CONCLUSIONS: In persons followed up for asbestos exposure, increased mesothelin levels signalize pathological processes in the chest and correlate with severity of the disease. The study suggests that mesothelin cannot be considered a reliable marker for the early stage of malignant degeneration of pleural disease but only an additional criterion for examination of the followed-up individuals.
Keywords: Mesothelioma; azbest; Incidence; Mesothelin; Česká republika; Middle Aged; ROC Curve; azbestóza; mužské pohlaví; GPI-Linked Proteins; nádory plic; mesothelin; incidence; maligní mezoteliom; Czech Republic; ROC křivka; Asbestosis; Biomarkers, Tumor; GPI-vázané proteiny; nádory pleury; ženské pohlaví; nádorové biomarkery; asbestos-exposed population; Occupational Exposure; Humans; mezoteliom; pracovní expozice; Asbestos; lidé středního věku; mezotelin; Mesothelioma, Malignant; malignant pleural mesothelioma; Female; Pleural Neoplasms; Lung Neoplasms; lidé; Male